New Romantic Imagining and Queering Tactics of English Pop in Early Thatcherite Britain and The Second British Invasion - Kallioniemi Kari; Jarman Freya; Richardson John; Pääkkölä Anna-Elena (International Center for Music Studies in University of Newcastle, 2022)
This article will take a look at how English popular music reacted to the early Thatcher era in Britain while at the same time gaining new global popular appeal, especially in the US, and imagining new radical politics connected with the role of sexual minorities